Risks measurement in banking: A bibliometric and content analysis. Issue 246 (13th September 2022) - Vashisht, Shailja; Sarva, Mahesh; Mundi, Hardeep Singh
Abstract: Banking risk has gained interest from researchers after the global financial crisis and implementation of Basel III norms. The present study performs a scientific bibliometric analysis of research on banking risk till data. Research has been conducted on five major types of banking risks – credit, operational, market, liquidity, and interest rate risk – from 967 publications on Scopus database from 1967 to 2021. The results suggest that the research in the area is dominated by the United States, the United Kingdom, and China. The publications in top journals in the domain of finance and economics are less, but the number has increased after 2008–2009. The paper also performs content analysis on top‐cited papers of five risk categories to find major themes and theoretical, practical, and methodological contributions. These findings suggest scope for more research in risks other than credit and operating risks, as existing research is centred around modelling risk and predicting default rates. Researchers in the area should focus on programming and machine learning tools. Regarding policy implications, the research identifies key publications in risk modelling, which can be used as the basis of improved supervisory mechanisms and internal controls.